A Fear Index to Predict Oil Futures Returns - Julien Chevallier; Benoît Sévi (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper evaluates the predictability of WTI light sweet crude oil futures by using the variance risk premium, i.e. the difference between model-free measures of implied and realized volatilities. Additional regressors known for their ability to explain crude oil futures prices are also considered, capturing macroeconomic, financial and oil-specific influences. The results indicate that the explanatory power of the (negative) variance risk premium on oil excess returns is particularly strong (up to 25% for the adjusted Rsquared across our regressions). It complements other financial (e.g. default spread) and oil-specific (e.g. US oil stocks) factors highlighted in previous literature.
Keywords: C32; G17; Q47; 330; Oil Futures; Variance Risk Premium; Forecasting